Fabrication of CoNiMo/γ-Al2O3 from waste aluminum foil to convert waste lube oil to hydrotreated oil - Asmaa A. Abdelrahman; Mohamed A. Sayed; Mohamed F. Menoufy; Abdelrahman M. Rabie (Egyptian Journal of Petroleum)
Because of the heavy metal content and other toxic chemicals, used lubricating oil remains one of the most serious environmental concerns. The target of this work is the synthesis of γ-Al2O3 from waste aluminum foil and re-refining waste lubricating oils using solvent extraction pursued by hydrotreatment. The trimetallic CoNiMo/γ-Al2O3 catalyst was prepared via a co-impregnation method. The support and tri-metallic supported alumina are characterized by N2 adsorption–desorption techniques, X-ray diffraction (XRD), Raman spectroscopy, HRTEM, and EDX. The catalyst was evaluated in the hydrotreating of extracted waste lubricating oils. The results confirmed that the solvent to oil ratio of 3 gave the higher performance with the highest percent of sludge elimination at room temperature. Hydrotreating of extracted lube oil was investigated to determine the effect of variables such as temperature, pressure, liquid hour space velocity, and hydrogen to oil feed ratio. The results indicated that the optimum conditions are (temperature 400 °C, Pressure 60 bar, 0.75 h−1 LHSV). The results showed improvement of the hydrotreated waste lubricating oils properties by decreasing the refractive index from 1.480 to 1.460, the total acid number decreased from 8.164 to 0. 459, the Viscosity Index increase from 78 to 129, and the Sulfur content decreased from 6752 ppm to 543 ppm.